Diffusion mechanism of silver particles in polymer binder for die attach interconnect technology - Omar, Ghazali; Esa, Siti Rahmah; Sheikh Md Fadzullah, Siti Hajar; Siow, Kim Shyong; Abdul Rahim, Bazura; Cosut, Bunyemin (Universiti Malaysia Perlis, 2020)
Sintered Ag has gained strong interest as an important alternative material for interconnect technology in wide bandgap (WBG) semiconductor industries specifically for high thermal dissipations and high-speed applications. This material typically consists of metallic particles bounded by polymer binder expected to diffuse at the temperature much lower than its melting temperature. This paper studies the diffusion mechanism between Ag particles and its microstructural change over different heat treatment temperature that leads to the understanding on the formation of bonding particles into a predominantly solid Ag network as a conducting path for the interconnect systems. The surface diffusion initiated between Ag particles as they come into intimate contact through the formation of necking. Further atomic movement and diffusion between the particles neck resulting in volume expansion, necking growth as well as the transformation of the particle shape from spherical into an elongated structure. This results in the formation of a long chain of connecting particles, which transform the Ag particles into a solid Ag network.